2022
DOI: 10.1186/s12986-022-00687-z
|View full text |Cite
|
Sign up to set email alerts
|

The potential mechanisms of lactate in mediating exercise-enhanced cognitive function: a dual role as an energy supply substrate and a signaling molecule

Abstract: Lactate has previously been considered a metabolic waste and is mainly involved in exercise-induced fatigue. However, recent studies have found that lactate may be a mediator of the beneficial effects of exercise on brain health. Lactate plays a dual role as an energy supply substrate and a signaling molecule in this process. On the one hand, astrocytes can uptake circulating glucose or degrade glycogen for glycolysis to produce lactate, which is released into the extracellular space. Neurons can uptake extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 100 publications
1
33
0
Order By: Relevance
“…Intense exercise generates both physical and cognitive fatigue [ 45 ], although long-term moderate exercise improves cognitive functions [ 46 ]. However, the mechanism of intense exercise to induce cognitive fatigue has remained controversial [ 45 , 47 , 48 ]. The present study demonstrated that EPPH improved physical and cognitive fatigue induced by exhaustive exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Intense exercise generates both physical and cognitive fatigue [ 45 ], although long-term moderate exercise improves cognitive functions [ 46 ]. However, the mechanism of intense exercise to induce cognitive fatigue has remained controversial [ 45 , 47 , 48 ]. The present study demonstrated that EPPH improved physical and cognitive fatigue induced by exhaustive exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is well-known to generate lactate, promote anti-inflammatory signaling, and enhance tissue repair. [160][161][162] This exercise-induced resolution-repair program repairs skeletal muscle that becomes injured through exercise. 163 The process is initiated by the recruitment of pro-inflammatory Ly6c hi monocytes by the chemokine CCL2.…”
Section: Supplementation Of Pro-resolving Mediators To Promote Macrop...mentioning
confidence: 99%
“…Aside from direct injection of lactate or boosting efferocytosis, lactate levels can be acutely raised through exercise. Exercise is well‐known to generate lactate, promote anti‐inflammatory signaling, and enhance tissue repair 160–162 . This exercise‐induced resolution‐repair program repairs skeletal muscle that becomes injured through exercise 163 .…”
Section: Targeting Macrophage Metabolism In Chronic Inflammatory Dise...mentioning
confidence: 99%
“…More importantly, burdensome specific metabolites (e.g., lactate) in one tissue may be important regulators in another organ, as lactate acts as a mediator of the beneficial effects of exercise on brain health. Lactate plays a dual role as an energy supply substrate and a signaling molecule in this metabolic coupling process [ 23 ]. This metabolic coupling process manifests.…”
Section: Qigong Exercise Balances the Whole Body By Accelerating Mate...mentioning
confidence: 99%